Load-Bearing Capacity of Bamboo Reinforced Beams: A Comparative Study of Flanged and Rectangular Cross-Sections (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The environmental impact of steel production has prompted the construction industry to seek sustainable alternatives for concrete reinforcement. This study evaluates bamboo as a viable substitute, emphasizing its structural performance in two beam geometries: T-beams and rectangular beams. Mature bamboo culms, aged 3–4 years and sourced from Gbokoto village in Ogun State, Nigeria, were carefully selected and subjected to rigorous pre-treatment and durability assessments—including Accelerated Aging and Graveyard tests in accordance with ASTM D1037-99 and BS 350:2016 standards—to ensure optimal mechanical properties and resistance to biological degradation. Bamboo-reinforced concrete beams were cast with uniform reinforcement ratios and mix designs, and flexural tests were conducted following ASTM and ISO standards. Treated bamboo splints demonstrated significantly enhanced tensile strength and durability compared to untreated samples. T-beams consistently outperformed rectangular beams in stiffness, load-bearing capacity, and ductility, attributed to their flanged geometry. Statistical analysis using ANOVA confirmed a significant difference in structural performance between the two geometries, underscoring bamboo’s potential as an eco-friendly and structurally reliable reinforcement material for modern concrete construction.